SALES FORCE AND INTELLIGENCE STRATEGIC IN SMES PERFORMANCE: CASE STUDY OF BATIK’S ENTERPRISES IN BRINGHARJO YOGYAKARTA - AHMAD JOHAN; DESSY ISFIANADEWI; TEZZA ADRIANSYAH ANWAR (Journal of Business Studies and Management Review, 2019)
The purpose of this study is to investigate how small & medium scale companies in managing Sales Forces owned & strategic intelligence in obtaining information amid complex competition with all its limitations. The context of Small & Medium Enterprises (SMEs). Sales Force is the key to the strength of organizational success. Frequent interaction with consumers & competitors brings up a dynamic concept which is defined as routine regulating other routines, that is, besides its function as a salesperson, it is tasked to gather the information. Activity in searching information through intelligence from sales is called activity intelligence. External information obtained by the company through the Sales Force will lead to strategic planning so as to encourage organization performance to be able to flexibly adjust current business trends. This study used a case study to answer the research questions. Four enterprises were chosen as cases in this study. The result shows that the Sales Force's role will have an impact on organization performance, but organizations that implement activity intelligence through sales forces will be far more flexible & active in adjusting the business before the competition starts. In addition, this study also found strong linkages for organizations that grow through Sales Force & Activity Strategic Intelligence in terms of improving organization Performance.